(untitled) (Agroindustrial Science, 2020)
Generally, chefs use garlic as an ingredient that enhances the sensory qualities of foods. However, recent studies have shown that garlic contains Sulphur compounds, which provide a health benefit. This review identifies and describes those constituents in garlic responsible for their anti-microbial, antioxidant, anti-inflammatory, and in some cases anti-cancer properties. Also, this review reports the chemical and nutritional contents of garlic (Allium sativum L.) and shows its health benefits for humans. A large variability and diversity in the nutritional content of garlic was found in the literature, including functional properties (antioxidant, antimicrobial, antifungal, and immunological), and many health benefit components, such as antihypertensive, hypolipidemic, antiatherogenic, anticarcinogenic, antitumor, antiaggregant, fibrinolytic, immunomodulatory, and antianemic. Allicin and ajoene were identified among some of the compounds in garlic which are beneficial for human health. Quantity varies depending on bulb maturity and harvest location, and values range between approximately 1mg/g and 9mg/g for allicin and 0.12 mg/g to 0.22 mg/g of garlic oil macerate for ajoene.